A Rare Cause of Palpable Purpura: Eosinophilic Granulomatosis with Polyangiitis - Teixeira, Ana Isabel (2016)
Eosinophilic granulomatosis with polyangiitis is a systemic vasculitis that affects small to medium vessels, belonging to the spectrum of antineutrophil cytoplasm antibody-associated vasculitis. It is a rare disease that presents with vasculitis, asthma and other eosinophilic symptoms. We present the case of a 67-year-old male, with a palpable purpura affecting the superior and inferior limbs, and abdomen, for the past month. The patient complained of chronic cough for the past year, which aggravated in the last month. Complementary studies allowed the diagnosis of eosinophilic granulomatosis with polyangiitis and the patient was treated with prednisolone until remission followed by azathioprine as a maintenance therapy. After one year of follow-up no recurrence was seen.